Oral Health Care for Children With Developmental Disabilities - Kenneth W. Norwood; Rebecca L. Slayton; Gregory S. Liptak; Nancy Murphy; Richard C. Adams; Robert T. Burke; Sandra Friedman; Amy J. Houtrow; Miriam A. Kalichman; Dennis Z. Kuo; Susan E. Levy; Kenneth W. Norwood; et al. (2013)
This Clinical Report was revised. See https://doi.org/10.1542/peds.2024-067603. Children with developmental disabilities often have unmet complex health care needs as well as significant physical and cognitive limitations. Children with more severe conditions and from low-income families are particularly at risk with high dental needs and poor access to care. In addition, children with developmental disabilities are living longer, requiring continued oral health care. This clinical report describes the effect that poor oral health has on children with developmental disabilities as well as the importance of partnerships between the pediatric medical and dental homes. Basic knowledge of the oral health risk factors affecting children with developmental disabilities is provided. Pediatricians may use the report to guide their incorporation of oral health assessments and education into their well-child examinations for children with developmental disabilities. This report has medical, legal, educational, and operational implications for practicing pediatricians.